The outcome of displaced intraarticular fracture of calcaneum: Open reduction and internal fixation with locking plates versus closed reduction and percutaneous K wires fixation - Dahal, Sunit; Dhakal, Sagar (Grande Medical Journal, 2024)
Background The treatment of displaced intraarticular fracture of the calcaneum is challenging because of complicated bony structure, complex fracture anatomy, fragile soft tissue, and difficulty in achieving anatomic reduction and rigid fixation. In this study, we aimed to compare the outcome treatment by percutaneous K wires fixation and locking plate osteosynthesis.Method The prospective study was conducted among patients who were admitted and operated on for calcaneum fractures in the Department of Orthopedics, Shaikh Zayed Postgraduate medical institute Lahore Pakistan from October 2014 to October 2015. Of the 30 cases, half received treatment with K-wire and the other half of the patients underwent plating. Pre- and post-operative Bohler’s and Gissane’s angles, the width of calcaneums, the height of posterior facet, and complications were noted for all patients. Functional outcome was assessed using the American Orthopaedic Foot and Ankle Society (AOFAS).Result Bohler’s angle and posterior facet height increased significantly postoperatively (p